ANALISIS PENGARUH MOTIVASI KERJA DAN FASILITAS KERJA TERHADAP KINERJA FOTOGRAFER JURNALISTIK PADA MEDIA HARIAN FAJAR DAN TRIBUN TIMUR MAKASSAR - Mau, Muliadi; Latif, Das'ad; Idham Ama, Muhammad (DIALEKTIKA KOMUNIKA: Jurnal Kajian Komunikasi dan Pembangunan Daerah, 2024)
This study aims to analyze the performance of journalistic photographers in Makassar City are: (1) To analyze the influence between work motivation on the performance of journalistic photographers. (2) To analyze the influence between work facilities on the performance of journalistic photographers, and (3) To analyze the influence between work ability, work motivation and work facilities on the performance of journalistic photographers, in Makassar City. This study applies a descriptive quantitative paradigm with purposive sampling technique, the population of 40 photographers working in print media and online media in Makassar City. The sample was three photographers at the East Tribune Daily and five photographers at Fajar Daily. Based on the results of data analysis, then it can be concluded as follows: (1) There is no influence between work motivation on the performance of journalistic photographers. (2) There is an influence between work facilities on the performance of journalistic photographers, and (3) Work motivation, and work facilities affect the performance of journalistic photographers in Makassar City.